Ethical Aspects of Artificially Administered Nutrition and Hydration: An ASPEN Position Paper. (22nd February 2021) - Schwartz, Denise Baird; Barrocas, Albert; Annetta, Maria Giuseppina; Stratton, Kathleen; McGinnis, Carol; Hardy, Gil; Wong, Theodoric; Arenas, Diego; Turon‐Findley, Mary Pat; Kliger, Rubén Gustavo; Corkins, Kelly Green; Mirtallo, Jay; et al.
Abstract: The American Society for Parenteral and Enteral Nutrition (ASPEN) Position Paper focus is on applying the 4 ethical principles for clinician's decision‐making in the use of artificially administered nutrition and hydration (AANH) for adult and pediatric patients. These basic principles are (1) autonomy, respect the patient's healthcare preferences; (2) beneficence, provide healthcare in the best interest of the patient; (3) nonmaleficence, do no harm; and (4) justice, provide all individuals a fair and appropriate distribution of healthcare resources. Preventing and resolving ethical dilemmas is addressed, with an emphasis on a collaborative, interdisciplinary approach. Optimizing early communication and promoting advance care planning, involving completion of an advance directive, including designation of a surrogate decision‐maker, are encouraged. Clinicians achieve respect for autonomy when they incorporate the patient, family, community, country, geographical, and presumed cultural values and religious belief considerations into ethical decision‐making for adults and children with a shared decision‐making process. These discussions should be guided by the 4 ethical principles. Hospital committees and teams, limited‐time trials, clinician obligation with conflicts, and forgoing of AANH are addressed. Specific patient conditions are addressed because of the concern for potential ethical issues: coma, decreased consciousness, and dementia; advanced dementia; cancer; eating disorders; and end‐stage disease/terminal illness. Incorporated in the Position Paper are ethical decisions during a pandemic and a legal summary involving ethical issues. International authors presented the similarities and differences within their own country or region and compared them with the US perspective.